Usage of social networking sites among underprivileged entrepreneurs: Effects of social capital and attachment / Sia Wan Qi - Sia , Wan Qi (2018)
This study reports on the use of Social Networking Sites (SNS) through social capital and attachment theoretical lens among underprivileged entrepreneurs. The main objective of the study is to examine relationships between social capital and SNS usage among the underprivileged communities, while taking into consideration the mediating effect of SNS attachment. This study employs quantitative method using a survey questionnaire to gather the data. A random sampling method disseminated at Malaysia Digital Economy Corporation (MDEC) events were used. The survey sample included underprivileged women entrepreneurs as the participants. A total of 381 questionnaires were distributed with a response rate of 81.6%. The valid data collected from survey was analysed using IBM SPSS statistics version 24 for descriptive statistic. Confirmatory Factor Analysis (CFA) was carried out to ensure convergent validity and discriminant validity by using SmartPLS 3.2.7 software. Path analysis was conducted on the data to determine the significance of the path or relationship between the independent and dependent variables. Model testing was conducted to validate the relationship among the hypothesis. The finding suggests underprivileged entrepreneurs are utilising SNS for business purposes through establishment of social capital by creating relationships with others and stimulate SNS attachment that increase the level of SNS usage. This research provides information for government agencies and non-governmental organizations (NGOs) in understanding the behaviour of underprivileged community in entrepreneurship ventures and can be used as input for government agencies formulating guidelines/policies to support underprivileged community entrepreneurs. The findings of this study could be used to design the best possible information services which can support the needs of this community to grow and sustain their business ventures.